Evaluasi dan re-disain tipologi ruang terbuka hijau (kasus daerah perkotaan di Provinsi Papua Barat) - Marlina Rumiris; Roni Bawole; Thomas Pattiasina (Cassowary, 2019)
In general, the presence of green open space as one element in the urban spatial is very weak and the potencial is reduced portion because they do not have a high economic value. One function of green open space is for micro-climate amelioration, making green open space as a lugs of the city for helping the formation of a cool and comfortable climate in the vicinity. This comfort is determined by the interdependence between the factors of air temperature, air humidity, light and wind movement. Vegetation can improve the quality of the local climate or reducing temperature named micro-climate amelioration function as well. This study aimed to evaluate and redesign the typology of green open space to create green resolution with conversion of carbon to compansate for changes in the landscape that occur as a result of ongoing development. The study was conducted in urban areas of West Papua Province with five cases were selected purposively. Refers to the Ministry of Public Work No. 5 of 2008 and some related references, the results of research (qualitative exploration research) showed that 3 of the 5 cases have not met the ideal typology of Green Open Spaces, while two other cases have met the ideal typology for ecological function, but remain in need of the final material. Redesigns of Green Open Spaces that has been generated from this study are expected to restore ecological functions with holding the ecologycal aspect as a priority matter to consider as well. Therefor those can be used by local goverments for planning repairs or improvements in the future.